Biofuel as Alternative Energy Carrier : Current Status, European Policies, Market and Production Level - Sharma, V.K.; Braccio, G.; Freda, C.; Antoshchuk, T.; Pyanykh, K.; Karp, I.; Zinoviev, S. (Энерготехнологии и ресурсосбережение, 2011)
Biofuels could be an appropriate way to reduce green house gas (GHG) emissions and to reduce the amount of fossil fuels burned. Two most common types of biofuels which are being developed and presently available on a commercial basis, are Ethanol and Biodiesel along with their derivatives. Biodiesel is the biofuel with the most rapid rate of market growth. European biodiesel industry is well established with a significant continuous increase in its production. In order to support the use of biodiesel and biofuel World-wide, especially, in developing countries where fossil energy use GHG emission will rise exponentially, there is a utmost necessity for international co-operation. The questions of biofuel industrial production, financial incentives, legislation, investment potential et. al. will be discussed in this publication.